Immunotherapy of Hepatocellular Carcinoma with Magnetic PD-1 Peptide-Imprinted Polymer Nanocomposite and Natural Killer Cells - Lee, Mei-Hwa; Liu, Kai-Hsi; Thomas, James L.; Chen, Jyun-Ren; Lin, Hung-Yin (Biomolecules (Basel, Switzerland), 2019)
Programmed cell death protein 1 (PD-1) is a biomarker on the surface of cells with a role in promoting self-tolerance by suppressing the inflammatory activity of T cells. In this work, one peptide of PD-1 was used as the template for molecular imprinting to form magnetic peptide-imprinted poly(ethylene-co-vinyl alcohol) composite nanoparticles (MPIP NPs). The nanoparticles were characterized by dynamic light scattering (DLS), high-performance liquid chromatography (HPLC), Brunauer–Emmett–Teller (BET) analysis, and superconducting quantum interference device (SQUID) analysis. Natural killer 92 (NK-92) cells were added to these composite nanoparticles and then incubated with human hepatoma (HepG2) cells. The viability and the apoptosis pathway of HepG2 were then studied using cell counting kit-8 (CCK8) and quantitative real-time polymerase chain reaction (qRT-PCR), respectively. These nanoparticles were found to significantly enhance the activity of natural killer cells toward HepG2 cells by increasing the expression of nuclear factor kappa B (NF-κB), caspase 8, and especially caspase 3.